Sexual risk behaviors among youth heads of household in Gikongoro, south province of Rwanda - Ntaganira Joseph; Hass Laura J; Hosner Sheila; Brown Lisanne; Mock Nancy B (BMC, 2012)
Abstract Background As a result of the 1994 genocide and AIDS, Rwanda has a crisis of orphans. In 2005, the Ministry of Local Governance and Social Affairs of Rwanda has reported one million vulnerable children. Many of these are not only orphans but also youth heads of households (YHH). The purpose of this study was to: (a) identify risk behaviors that expose YHH to HIV infection, (b) determine gender-specific high risk profiles and, (c) determine predictors of sexual onset. Methods A household survey was conducted among 692 YHH, aged 12-24, all beneficiaries of a World Vision basic needs program in Gikongoro, Rwanda, from January to March 2004. Participants were interviewed using a structured questionnaire. Data was collected on socio-demographic variables, HIV/AIDS prevention knowledge and sexual risk behaviors. Bivariate analyses of the study variables were performed to examine differences between males and females. A logistic regression analysis was conducted to analyze factors that were independently associated with the debut of having sex. Results Forty-one percent of respondents reported sexual onset before age 15. Males were more likely to start earlier than females (50.4% versus 26.7%) but females reported more sexual onset with an older partner. Fifty-eight percent of females had their first intercourse with a partner who was four or more years older than themselves. While sexual activity was low (1.75 mean lifetime sexual partner, 0.45 mean sexual partner last twelve months), sexual experience was related to less social connectedness and use of drugs. Having a close friend also appeared to be protective for sexual debut. The analysis also found that although YHH were aware of some prevention measures against HIV/AIDS, there was low (19.8%) knowledge of the "ABC" prevention program promoted by the government. In addition, despite 85% of respondents knowing someone who had died of AIDS, only 31% perceived themselves at risk of HIV infection, and there was very low (13.2%) condom use among the sexually experienced. Conclusions Results suggest the urgent need of HIV prevention programs tailored to YHH that provide knowledge, enhance negotiations skills, and increase the perception of HIV infection risk among YHH in Rwanda.